Diseño y desarrollo tecnológico de un equipo de envasado didáctico para el laboratorio de control de producción de la Fundación Universidad de América (2018)
For the development of the Research Project, a diagnosis of the current state of the equipment was made, where the parameters to be modified and the elements that could be used were found. After that, the conceptual and functional design was started based on the requirements of the University laboratory, and being clear about the operation, the automated packaging system was developed together with the elements that made it up. The manufacturing stage corresponded to the Ingenium company, the commissioning and test tests were carried out; finally manuals and laboratory guides for the area of industrial engineering and industrial automation were developed. The team is at the service of the students of the University of America to perform the corresponding practices according to the guidelines provided.